Dismembered Asian/American Android Parts in Ex Machina as ‘Inorganic’ Critique - Wong, Danielle (Transformations, 2017)
This paper analyses the dismemberment and dispersal of Asian/American android-coolie parts in the sci-fi film Ex Machina (2015) in order to theorise an inorganic critique of the postracial-as-posthuman subject. By turning to Asian/American robot self-dismemberment and the dispersal of their fragments, I address this special issue’s interest in human-robot relationships and social robotics not only by highlighting the historical techno-Orientalist configurations of the Asian labourer as machine, but by considering how the so-called inorganic nature of the robot characterises the circulations of racialised — particularly Asian/American — performance and spectral labour that disrupt white-as-postracial, posthuman futurity. This paper looks at two modes of Asian/American dismemberment in Ex Machina that cause “glitches” in the white social body’s reproductive wholeness: the removable Asian/American face as counter-surveillance and the transferrable nature of Asianness as a proxy (a reiteration of the model minority) that threatens to breach white subjectivity.